Dinamika Hukum Agraria dan Urbanisasi: Pengelolaan Hak Guna Ruang Bawah Tanah di Kota-Kota Besar Indonesia - Lubis, Ikhsan; Siregar, Taufik; Lubis, Duma Indah Sari; Lubis, Andi Hakim (Fakultas Hukum Universitas Bangka Belitung, 2024)
This study addresses the main legal issue concerning the management of underground space in major cities in Indonesia amid rapid urbanization. The current regulations, such as the Basic Agrarian Law, do not provide clear provisions regarding the right to use underground space, leading to legal uncertainty and potential conflicts of interest. The position of this research is to analyze existing regulations through a normative juridical approach and propose legal solutions that are more adaptive to the needs of urban modernization. This paper examines the limitations of current regulations and suggests the need for more comprehensive, specific legislation governing underground space rights. The main findings of this study reveal the inadequacy of the existing legal framework in accommodating the management of underground space fairly and sustainably, and the urgency for regulatory reforms that are more responsive to Indonesia’s urbanization developments.